2016
DOI: 10.1007/s11258-016-0624-7
|View full text |Cite
|
Sign up to set email alerts
|

Land-use change under a warming climate facilitated upslope expansion of Himalayan silver fir (Abies spectabilis (D. Don) Spach)

Abstract: Global warming is triggering some species to shift towards the poles or higher elevations, but spatial translocation is also influenced by land-use regime or intensity. The Himalayan climate is getting warmer and land use has changed, reducing in intensity in some areas. We estimated the upper species limit (USL) and tree limit of Abies spectabilis (D. Don) Spach and assessed whether these have changed over recent years. We hypothesise an upslope shift in response to enhanced temperature and changes in land-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“… and references therein, Suwal et al. ), and the phenological response of species (e.g., Shrestha et al. , Hart et al.…”
Section: Introductionmentioning
confidence: 99%
“… and references therein, Suwal et al. ), and the phenological response of species (e.g., Shrestha et al. , Hart et al.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of vegetation in temperate forest in Lachung Range of the Sikkim Himalaya recorded the minimum adult density of L. griffithiana and Populus jacquemontiana (Subba et al 2015). In temperate and subalpine forests of Nepal, spatially heterogeneous distribution of seedlings and saplings was observed in other tree species such as Quercus semecarpifolia in LNP (Vetaas 2000), Betula utilis in Manang (Shrestha et al 2007) and LNP (Kunwar 2011), and Abies spectabilis in MCA and Gaurishankar Conservation Area (Suwal et al 2016). The small population of L. himalaica in LNP deserves further investigations considering the influence of natural or anthropogenic factors and management interventions.…”
Section: Discussionmentioning
confidence: 98%
“…Sustainability of populations with inadequate number or lack of regenerating individuals has been reported to be challenging for several species of subalpine trees. Examples include Larix potaninii in China (Taylor et al 1996;Cui et al 2017;Liang and Wei 2020), Larix griffithiana in Sikkim, India (Tambe et al 2011;Subba et al 2015), and Bhutan (Moktan 2010); and for many other species in the eastern Himalaya (Pandey et al 2018), Nepal Himalaya (Vetaas 2000;Shrestha et al 2007;Kunwar 2011;Sujakhu et al 2013;Maren et al 2015;Suwal et al 2016), and western Himalaya (Rai et al 2012). Therefore, for the effective conservation of the typical Himalayan vegetation of Larix forests, efforts need to be concentrated both locally and regionally.…”
Section: Parametermentioning
confidence: 99%
“…In this study, we focused on the Himalayan elevation gradient in Nepal because 1) it is one of the longest and steepest elevational gradients in the world, 2) it is a global hotspot of biodiversity (Mittermeier et al 2004), 3) global warming is forcing numerous treeline species along this gradient to move upward at a rate as high as 26 m per decade (Chhetri et al 2018, Gaire et al 2014, Suwal et al 2016, and 4) the distribution of species along an elevational gradient according to Rapoport's elevational rule can be tested along this gradient. Some studies have reported unimodal patterns in tree species elevational ranges along this elevational gradient (Bhattarai & Vetaas 2006, Vetaas & Grytnes 2002, while others have reported a monotonic increase in elevational ranges among other groups of plant species (Feng et al 2016, Subedi et al 2020) supporting Rapoport's elevational rule.…”
Section: Rapoport's Elevational Rulementioning
confidence: 99%